2015
DOI: 10.1128/jvi.00157-15
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Protein Phosphatase 2A Targeting by Merkel Cell Polyomavirus Small T Antigen

Abstract: Merkel cell polyomavirus (MCV) is a newly discovered human cancer virus encoding a small T (sT) oncoprotein. We performed MCV sT FLAG-affinity purification followed by mass spectroscopy (MS) analysis, which identified several protein phosphatases (PP), including PP2A A and C subunits and PP4C, as potential cellular interacting proteins. PP2A targeting is critical for the transforming properties of nonhuman polyomaviruses, such as simian virus 40 (SV40), but is not required for MCV sT-induced rodent cell transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 70 publications
3
71
0
Order By: Relevance
“…This negative finding was affirmed by our present study, in which MCPyV sT did not affect the phosphorylation status of pRb. Additionally, a report by Kwun et al confirms the limited MCPyV sT-PP2A binding capacity and suggests that the oncogenic capabilities of MCPyV sT may be attributed to its interactions with ubiquitin E3 ligases rather than PP2A [14]. Thus, the oncogenic action of MCPyV sT does not appear to rely on PP2A or its substrates [4,14].…”
Section: Discussionmentioning
confidence: 57%
“…This negative finding was affirmed by our present study, in which MCPyV sT did not affect the phosphorylation status of pRb. Additionally, a report by Kwun et al confirms the limited MCPyV sT-PP2A binding capacity and suggests that the oncogenic capabilities of MCPyV sT may be attributed to its interactions with ubiquitin E3 ligases rather than PP2A [14]. Thus, the oncogenic action of MCPyV sT does not appear to rely on PP2A or its substrates [4,14].…”
Section: Discussionmentioning
confidence: 57%
“…MCV sT is generated from alternative splicing of the T antigen encoding gene to form an iron-sulfur protein with an unclear function for the virus (20,42). Similar to other polyomavirus sT proteins, MCV sT binds and inactivates some PP2A isoforms (43); however, it is transforming in rodent cells (44) and induces cell proliferation and tumorigenicity in transgenic mice (45)(46)(47). Its transforming activity has been mapped to a domain called the LT stabilization domain (LSD) that is separate from its PP2A-binding motif, and the LSD promiscuously binds SCF and anaphase-promoting complex E3 ligases (22,48).…”
Section: Discussionmentioning
confidence: 99%
“…The pathobiological effects and mechanisms of polyomavirus sT antigens are complex and dependent on the characteristics of different viruses as well as the specific tissue/cell context [7,8,18]. Computer-assisted genomic analysis of MCPyV, TSPyV, HPyV6, and HPyV7 demonstrated that all four sT antigens share an N-terminal DnaJ domain followed by protein phosphatase 2A-binding sequences and zinc-finger motifs [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, polyomavirus small T (sT) antigens are strongly associated with cell proliferation pathways [6,7,8,9]. For example, in a previous report, we showed that TSPyV sT antigen activates the MEK-ERK-c-Jun pathway [7].…”
Section: Introductionmentioning
confidence: 99%